Naturalistic Speech-Generating Device Interventions for Children With Complex Communication Needs: A Systematic Review of Single-Subject Studies - Gevarter, Cindy; Zamora, Claudia (American journal of speech-language pathology, 2018)
This article presents a systematic review that aimed to synthesize single-subject-design studies that have examined naturalistic interventions for teaching the expressive use of speech-generating devices (SGDs) to children with complex communication needs. Specifically, this review describes what intervention strategies are most commonly applied in studies with positive effects and minimal methodological flaws and examines the populations and outcomes for which these strategies have been effective. A systematic approach was used to qualitatively code variables of interest to this review. Results were summarized via both visual analysis and effect size methods, and a certainty of evidence methodology was adopted to describe the quality of the evidence. Thirty-two unique studies met inclusion criteria, with 19 having consistent positive results and meeting minimum requirements for certainty of evidence. Although studies used a variety of titles to describe intervention packages (e.g., milieu teaching, interaction strategies), certain strategies were common across studies. These included (a) creating and capturing communication opportunities via methods such as time delay and questioning; (b) providing feedback via methods such as reinforcement of requests, praise, or expansions; (c) prompting (verbal, physical, gestural); (d) modeling; and (e) training communication partners. Findings regarding these intervention components help to provide practical guidelines for naturalistic SGD intervention. Limitations of the current body of research (e.g., need to include more home-based studies and more intermediate to advanced SGDs, need to critically analyze the most critical intervention components) provide suggestions for future research. https://doi.org/10.23641/asha.6615332.